A latex flocculation method, rubber masterbatch and preparation method and rubber composition
By using phytic acid as a flocculant in latex, the problems of long flocculation time and environmental pollution in the existing rubber wet kneading technology are solved, and the rapid flocculation and cleaning-free process is achieved, which improves the anti-aging performance of rubber products.
Patent Information
- Application Number
- CN202410035844.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-10
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-01-10
AI Technical Summary
In the existing rubber wet mixing technology, the latex flocculation process has problems such as long flocculation cycle, generating a large amount of acid wastewater, and being unfavorable to the environment and operators.
Phytic acid is used as a flocculant, and an appropriate amount of phytic acid is added to the latex, and the reaction with the latex is achieved by stirring to achieve rapid flocculation, and the solid rubber is directly dehydrated without cleaning.
The flocculation time is shortened, the production water consumption and the energy consumption of rubber washing are reduced, and phytic acid has anti-aging properties, which can replace anti-aging agents and improve the performance of rubber products.
Smart Images

Figure BDA0004657683570000031 
Figure BDA0004657683570000081
Abstract
Description
Technical Field
[0001] The invention relates to the field of rubber wet mixing, and more specifically to a latex flocculation method, a rubber masterbatch and a preparation method thereof, and a rubber composition. Background Art
[0002] Natural latex is a natural polymer emulsion synthesized by rubber trees through photosynthesis. Its main component is rubber hydrocarbon, and the rest are non-rubber substances such as proteins, fatty acids and sugars. As a general-purpose rubber, natural rubber (NR) has good tensile properties, wear resistance and elasticity, and is widely used in industrial and agricultural, medical and daily life rubber products.
[0003] The rubber particles in natural latex have a protective layer formed by hydrophilic substances such as charged proteins and lipids, which enables the latex to maintain a stable colloidal state. Therefore, destroying or weakening the protective effect of the protective layer on the surface of rubber particles can cause the latex to lose stability and flocculate. Natural rubber is prepared through the steps of natural latex collection and flocculation, gel block cleaning and drying, among which natural latex flocculation is an important process in the preparation of natural rubber. Adding acid, inorganic salts, microorganisms, heating or freezing can all cause natural latex to flocculate. The flocculation method can affect the structure of natural rubber, thereby affecting the performance of natural rubber.
[0004] Solid rubber can be obtained after latex is flocculated. In the prior art, hydrochloric acid and sulfuric acid are used for flocculation. The flocculation process is not completed instantly. The fresh latex after adding acid only thickens. After a period of time, clots are gradually formed. The flocculation cycle is long and the rubber needs to be repeatedly washed after precipitation, which will produce a large amount of acid wastewater, causing environmental pollution and adversely affecting the health of operators. Therefore, the flocculation process needs further improvement and development. Summary of the invention
[0005] In view of the various deficiencies of the prior art and in order to solve the above problems, a latex flocculation method, a rubber masterbatch and a preparation method and a rubber composition are proposed, and the following technical solutions are provided:
[0006] A latex flocculation method, wherein phytic acid is added to the latex to form solid rubber.
[0007] Furthermore, the amount of phytic acid added is 0.5-0.8wt% of the amount of solid rubber in the latex.
[0008] Furthermore, after the phytic acid is added to the latex, the latex is left to stand for 1-2 hours and then directly dehydrated without washing to obtain the solid rubber.
[0009] Furthermore, the phytic acid is added dropwise to the latex, and the latex is stirred during the adding process, and the stirring speed is 50-80 rpm.
[0010] In addition, the present invention also provides a method for preparing a rubber masterbatch, wherein fillers are added to latex and then flocculated using the above-mentioned latex flocculation method to obtain the rubber masterbatch, wherein the fillers do not include an antioxidant.
[0011] Furthermore, the filler comprises a modified silica slurry, and the modified silica slurry comprises nanocellulose with a fibrillation degree of 10-15%, a Gemini surfactant and a silica aqueous solution.
[0012] Furthermore, the preparation method of the modified silica slurry is as follows: adding nanocellulose to a silica aqueous solution and performing ultrasound treatment, and then adding a Gemini surfactant and stirring to obtain the modified silica slurry.
[0013] In addition, the present invention also provides a rubber masterbatch, which is prepared by the above-mentioned method for preparing the rubber masterbatch.
[0014] In addition, the present invention also provides a rubber composition, which is prepared by mixing and vulcanizing the above-mentioned rubber masterbatch, a vulcanizing agent and an accelerator.
[0015] Due to the adoption of the above technical solution, the beneficial technical effects of the present invention are:
[0016] 1. The present invention firstly creatively utilizes phytic acid to flocculate latex, the flocculation speed is fast, the flocculation time is shortened, and there is no need to wash the rubber material multiple times after flocculation, thus realizing a cleaning-free process, which can greatly reduce the production water consumption and rubber washing energy consumption.
[0017] 2. The phytic acid of the present invention can flocculate latex on the one hand, and can also replace antioxidants on the other hand, thereby improving the anti-aging properties of rubber products.
[0018] 3. The rubber composition of the present invention does not need to add additional antioxidants, and its anti-aging performance is comparable to the anti-aging performance of rubber added with antioxidants in the prior art. DETAILED DESCRIPTION
[0019] In order to enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention is clearly and completely described below in conjunction with the embodiments of the present invention. Based on the embodiments in this application, other similar embodiments obtained by ordinary technicians in this field without making any creative work should all fall within the scope of protection of this application.
[0020] The structure of phytic acid is shown below. 1 mol of phytic acid contains 12 mol of hydrogen ions, showing strong acidity.
[0021]
[0022] Biomass phytic acid comes from plants, is easily soluble in water, and has strong acidity. Compared with hydrochloric acid, sulfuric acid, phosphoric acid, etc., 1 mol of hydrochloric acid, sulfuric acid, and phosphoric acid contain 1 mol, 2 mol, and 3 mol of hydrogen ions respectively. 1 mol of phytic acid can provide 12 mol of hydrogen ions, which is 12 times that of hydrochloric acid, 6 times that of sulfuric acid, and 4 times that of phosphoric acid.
[0023] A latex flocculation method comprises the following steps: adding phytic acid to the latex to form solid rubber. The phytic acid is creatively applied to the latex flocculation process, which can increase the flocculation speed of the latex. Moreover, the phytic acid has good compatibility with the rubber, and the flocculant does not need to be washed out by a large amount of water, thus realizing a non-cleaning process and significantly reducing the production water consumption and rubber washing energy consumption.
[0024] In addition, due to the properties of phytic acid itself, the amount used for flocculating latex is greatly reduced. The amount of flocculant added in the prior art is generally 1-10wt% of the solid gum in the latex. However, when using phytic acid, only 0.5-0.8wt% of the solid gum in the latex is needed to completely flocculate the latex.
[0025] After adding phytic acid to latex, solid rubber can be obtained by standing it for 1-2 hours and then directly dehydrating it without washing. Phytic acid in rubber does not need to be washed away with water, and phytic acid has anti-aging properties in rubber and can replace antioxidants.
[0026] Specifically, phytic acid is added dropwise into the latex for flocculation, and the latex is stirred while the phytic acid is added dropwise at a stirring speed of 50-80 rpm.
[0027] In addition, the present invention also provides a method for preparing a rubber masterbatch, wherein fillers are added to latex and then flocculated according to the above flocculation method, phytic acid is used for flocculation, and an antioxidant does not need to be added to the latex.
[0028] The filler can be white carbon black slurry. Specifically, the white carbon black slurry of the present application is a modified white carbon black slurry, and the white carbon black is modified by using nanocellulose with a fibrillation degree of 10-15% and Gemini twin surfactant. The preparation method of the modified white carbon black slurry is as follows: nanocellulose is added to a white carbon black aqueous solution for ultrasonication, and Gemini twin surfactant is added after ultrasonication and stirred to obtain the modified white carbon black slurry. First, nanocellulose increases the steric hindrance between the white carbon black particles and reduces the agglomeration of the white carbon black particles. Nanocellulose can form a three-dimensional hydrogen bond network structure in water, which can stably disperse the white carbon black suspension. Nanocellulose is wrapped on the surface of the white carbon black particles. At this time, Gemini twin surfactant is added, and the hydrophilic end of the Gemini twin surfactant is combined with the nanocellulose, and the lipophilic end of the Gemini twin surfactant is combined with the latex, thereby achieving stable dispersion of white carbon black in the latex.
[0029] Example 1 Latex flocculation method
[0030] 1 kg of natural latex with a solid content of 60 wt % was selected, and 3.6 g of phytic acid was added dropwise while stirring for flocculation. The flocculation condition was observed. After 1.5 hours, the latex was completely flocculated, and then it was directly dehydrated and dried without washing to obtain solid rubber.
[0031] Example 2 Latex flocculation method
[0032] 1 kg of natural latex with a solid content of 60 wt % was selected, 3 g of phytic acid was added dropwise while stirring for flocculation, and the flocculation condition was observed. After 2 hours, the latex was completely flocculated, and then it was directly dehydrated and dried without washing to obtain solid rubber.
[0033] Example 3 Latex flocculation method
[0034] 1 kg of natural latex with a solid content of 60 wt % was selected, and 4.8 g of phytic acid was added dropwise while stirring for flocculation. The flocculation condition was observed. After 1 hour, the latex was completely flocculated, and then it was directly dehydrated and dried without washing to obtain solid rubber.
[0035] Example 4 Rubber composition
[0036] 1 kg of natural latex with a solid content of 60 wt % is used, and a modified white carbon black slurry is added to the natural latex, wherein the content of white carbon black in the modified white carbon black slurry is 180 g. After stirring for 30 minutes, 3.6 g of phytic acid is added dropwise while stirring for flocculation, and the flocculation is observed. After 1.5 hours, the latex is completely flocculated, and then it is directly dehydrated and dried without washing to obtain a rubber masterbatch. The obtained rubber masterbatch is mixed with 2.5 g of sulfur and 0.5 g of vulcanization accelerator M, and vulcanized to obtain a rubber composition. The preparation process of the white carbon black slurry is as follows: nanocellulose with a filament brooming degree of 15% is added to a white carbon black aqueous solution with a mass fraction, and after stirring and ultrasonicating for 30 minutes, a potassium carboxylate Gemini surfactant of 6% of the amount of white carbon black is added, and stirred for 60 minutes to obtain.
[0037] Example 5 Rubber composition
[0038] 1 kg of natural latex with a solid content of 60 wt % is used, and a modified white carbon black slurry is added to the natural latex, wherein the content of white carbon black in the modified white carbon black slurry is 120 g. After stirring for 30 minutes, 3 g of phytic acid is added dropwise while stirring for flocculation, and the flocculation is observed. After 2 hours, the latex is completely flocculated, and then it is directly dehydrated and dried without washing to obtain a rubber masterbatch. The obtained rubber masterbatch is mixed with 2.5 g of sulfur and 0.5 g of vulcanization accelerator M, and vulcanized to obtain a rubber composition. The preparation process of the white carbon black slurry is as follows: nanocellulose with a filamentization degree of 10% is added to a white carbon black aqueous solution with a mass fraction of 20%, and after stirring and ultrasonicating for 30 minutes, a potassium carboxylate Gemini surfactant of 5% of the amount of white carbon black is added, and stirred for 60 minutes to obtain.
[0039] Example 6 Rubber composition
[0040] 1 kg of natural latex with a solid content of 60 wt % was used, and a modified white carbon black slurry was added to the natural latex, wherein the content of white carbon black in the modified white carbon black slurry was 300 g. After stirring for 30 minutes, 4.8 g of phytic acid was added dropwise while stirring for flocculation, and the flocculation was observed. After 1 hour, the latex was completely flocculated, and then it was directly dehydrated and dried without washing to obtain a rubber masterbatch. The obtained rubber masterbatch was mixed with 2.5 g of sulfur and 0.5 g of vulcanization accelerator M, and vulcanized to obtain a rubber composition. The preparation process of the white carbon black slurry is as follows: nanocellulose with a filamentization degree of 15% was added to a white carbon black aqueous solution with a mass fraction of 10%, and after stirring and ultrasonicating for 30 minutes, 8% of the amount of white carbon black was added with a sodium carboxylate Gemini surfactant, and stirred for 60 minutes to obtain.
[0041] Comparative Example 1
[0042] 1 kg of natural latex with a solid content of 60 wt % was selected, and 12 g of hydrochloric acid was added dropwise while stirring for flocculation. The flocculation condition was observed. After 5 hours, the latex was completely flocculated. The hydrochloric acid in the rubber needed to be washed, and then dehydrated and dried to obtain solid rubber.
[0043] Comparative Example 2
[0044] 1 kg of natural latex with a solid content of 60 wt % was selected, and 3.6 g of hydrochloric acid was added dropwise while stirring for flocculation. The flocculation condition was observed and the latex could not be completely flocculated. The hydrochloric acid in the rubber obtained by flocculation needed to be cleaned and then dehydrated and dried to obtain solid rubber.
[0045] Comparative Example 3
[0046] 1 kg of natural latex with a solid content of 60 wt % was added with white carbon black slurry, wherein the mass fraction of the white carbon black slurry was 15% and the content of white carbon black in the white carbon black slurry was 180 g. After stirring for 30 minutes, 12 g of hydrochloric acid was added dropwise while stirring for flocculation. The flocculation condition was observed. After 5 hours, the latex was completely flocculated. Then, it was directly dehydrated and dried without washing to obtain a rubber masterbatch. The obtained rubber masterbatch was mixed with 2.5 g of sulfur and 0.5 g of vulcanization accelerator M and vulcanized to obtain a rubber composition.
[0047] Comparative Example 4
[0048] Compared with Example 4, the amount of phytic acid added is 3 grams, and the other steps are the same as Example 4.
[0049] Comparative Example 5
[0050] Compared with Example 4, the added amount of phytic acid is 7.2 g, and the other steps are the same as Example 4.
[0051] First, it can be seen from Examples 1-3 and Comparative Examples 1-2 that, compared with hydrochloric acid, phytic acid can quickly flocculate latex, especially in Comparative Example 2, when the amount of hydrochloric acid and phytic acid is the same, within the same flocculation time, phytic acid can completely flocculate latex, while hydrochloric acid cannot completely flocculate. The liquid added with hydrochloric acid in Comparative Example 2 will produce flocculation precipitation when flocculated again, while the liquid added with phytic acid in Example 1 will not produce flocculation precipitation when flocculated again. This fully proves that the flocculation effect of phytic acid is far better than that of hydrochloric acid.
[0052] The rubber compositions obtained in Examples 4-6 and Comparative Examples 3-5 were tested for ozone aging resistance and mechanical properties. First, the rubber compositions obtained in Examples 4-6 and Comparative Examples 3-5 were tested for ozone aging resistance according to method B in GB / T7762-2003 "Static tensile test of ozone cracking resistance of vulcanized rubber or thermoplastic rubber" (under specified tensile conditions, the time required for the first crack to appear is used as the ozone resistance of the evaluation sample). Mechanical properties were tested according to GB / T528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber".
[0053] Table 1 Mechanical properties and ozone aging resistance test results of rubber compositions
[0054]
[0055] As can be seen from Table 1 above, the mechanical properties and heat aging resistance in Example 4 are the best in comprehensive terms. It can be seen that phytic acid as a flocculant not only has a good flocculation effect, but also can be used as an antioxidant to improve the anti-aging performance of the rubber composition. Compared with the rubber composition in Comparative Example 3 that uses hydrochloric acid for flocculation and does not add an antioxidant, its anti-aging performance effect is significant, which fully illustrates that phytic acid plays an anti-aging role in the rubber material. When the amount of phytic acid is too little, the flocculation speed is reduced, and the anti-aging performance is reduced. When the amount of phytic acid is too much, it will affect the mechanical properties. As can be seen from Table 1 above, Comparative Example 5 has an effect on the natural latex itself due to the excessive amount of phytic acid, and its tensile properties and elongation at break are compared with Example 1, which are reduced by about 30%. In summary, the use of an appropriate amount of phytic acid can quickly flocculate the latex, while avoiding the cleaning of the rubber material and saving water consumption. More importantly, phytic acid has anti-aging properties, and anti-aging properties can be achieved without adding additional aging agents.
[0056] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a rubber masterbatch, characterized in that: Adding fillers to latex and then flocculating to obtain a rubber masterbatch, wherein the fillers do not include an antioxidant; The flocculation method comprises: adding phytic acid to latex to form solid rubber, wherein the amount of phytic acid added is 0.5-0.8wt% of the solid rubber in the latex, and the phytic acid is added to the latex and then allowed to stand for 1-2 hours without washing and then directly dehydrated to obtain the solid rubber; The phytic acid is added dropwise into the latex, and the latex is stirred during the adding process, and the stirring speed is 50-80 rpm.
2. The method for preparing a rubber masterbatch according to claim 1, characterized in that: The filler comprises modified white carbon black slurry, and the modified white carbon black slurry comprises nano cellulose with a fibrillation degree of 10-15%, a gemini surfactant and a white carbon black aqueous solution.
3. The method for preparing a rubber masterbatch according to claim 2, characterized in that: The preparation method of the modified silica slurry is as follows: adding nanocellulose to a silica aqueous solution for ultrasonic treatment, and adding a Gemini surfactant after ultrasonic treatment to stir to obtain the modified silica slurry.
4. A rubber masterbatch, characterized in that: The rubber masterbatch is prepared by the method for preparing the rubber masterbatch according to any one of claims 1 to 3.
5. A rubber composition, characterized in that: The rubber composition is prepared by mixing and vulcanizing the rubber masterbatch as claimed in claim 4, a vulcanizing agent and an accelerator.
Citation Information
Patent Citations
Rubber composition containing modified nano white carbon black and preparation method of rubber composition
CN107266745A
Preparation method of nano kaolin filled powder rubber
CN115725125A